Preservation of neural tissue with a formaldehyde‐free phenol‐based embalming protocol. Issue 2 (31st October 2018) - Tomalty, Diane; Pang, Stephen C.; Ellis, Randy E.
Abstract : The adverse effects formaldehyde fixation has on tissues both gross anatomically and histologically are well documented. Consequently, researchers are seeking alternative embalming techniques that better preserve in vivo characteristics of tissues. Phenol‐based embalming is one method that has shown promise in its ability to adequately preserve the in vivo qualities of tissues through preliminary explorations at the gross anatomical level. The literature on phenol‐based embalming is currently scarce, especially with regard to its effects on tissues at the microscopic level. For the current study we aimed to document the histologic effects of a formaldehyde‐free phenol‐based embalming solution on neural tissue, with the hope of providing novel insight into the effects of soft‐embalming on tissues at the microscopic level. Cerebral and cerebellar tissue obtained from porcine brains was fixed in phenol‐ and formaldehyde‐based fixatives; the latter served as a control. Fixed samples were processed for histological analysis. The phenol‐based embalming solution provided excellent preservation of the cerebral and cerebellar tissue morphology. Of note was the decrease in separation artifact seen in both tissue types relative to the control tissue, as well as anomalous circular artifacts in the white matter. The results of this study indicate that the phenol‐based embalming solution preserves neural tissue at the histological level, perhaps superiorly in many aspects when compared to the formaldehyde‐fixed samples. Further investigations of both gross anatomy and histology are recommended on the basis of these promising new findings to determine its potential utilities within research and education. Clin. Anat. 32:224–230, 2019. © 2018 Wiley Periodicals, Inc.